The influence of school principal leadership and work motivation on teaching quality of teachers at state vocational schools in oku timur - Mersissusanto Mersissusanto; Bukman Lian; Alhadi Yan Putra (Journal of Educational and Learning Studies, 2021)
The purpose of this study was to describe and analyze the influence of three independent variables including principal leadership and work motivation on teacher teaching quality. This research is a type of quantitative research. The population in this study amounted to 133 people from a number of State Vocational Schools institutions in OKU Timur. The data collection techniques used were questionnaires, interviews, observation and documentation. The data analysis technique in this study was started by using inferential statistics which included normality, homogeneity, linearity, simple linear correlation test, multiple correlation test, T test, and f test. The results of this study are (1) principal leadership has a positive effect on the quality of teacher teaching, (2) work motivation has a positive effect on the quality of teacher teaching, and (3) principal leadership and teacher work motivation simultaneously have a positive effect on teacher teaching quality.